Reticulocyte Parameter Analysis in the Automated Haematology Analyzer used in the Laboratories (Bangladesh Journal of Medicine, 2013)
Background: Reticulocyte count with immature reticulocyte fraction (IRF) used in the laboratories to evaluate the bone marrow erythropoietic activity and have great diagnostic and prognostic importance in the treatment of anemias and other pathological conditions. Objective: The aim of this study was to establish the normal reference range for reticulocyte count and its parameter. Methods: In this study reticulocyte profile were evaluated by automated analysis in 40 healthy control subjects by XT-2000i (Sysmex) hematology analyzer and compared with measurements obtained by manual methods. Manually reticulocytes were supravitally stained with new methylene blue. Results: This study found MRC was 0.81 ±0.46%. The FCMR was 0.97±0.17%, Ret abs was found .04±.02(106/ ?l) and IRF was found 3.92±1.35%. Conclusion: The precision of the automated analyzer was found significantly higher than the manual methods. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13616 Bangladesh J Medicine 2010; 21: 80-83